ANALYSIS OF MONTHLY PRODUCTION SCHEDULING USING ORE BLENDING STRATEGY TO FULFILL CONSERVATION PROCESS CASE STUDY GAG NICKEL MINE - Andi Milwadi; Heru Anggara; Adella Miranda; Gembong S Wibowo Wibowo (PERHAPI, 2022)
Gag Nickel mine is one of the mining projects in West Papua, Indonesia developed by Antam. Overall amount of reserve owned by this mine is 66 million wmt of nickel ore, with average nickel content 1.85%. In 2023, this mine will be projected to supply 3 million nickel ore to nickel processing plant, with minimum nickel content 1.80% and maximum SiO2/MgO ratio 2.4. Based on block model data, central zone area, consists of A and B pit are carried out to determine the potencies of both pits to meet production target. From pit A, 1.5 million wmt can be obtained, with average Ni 1.83% and SiO2/MgO ratio 2.07. While from pit B, there are 1.5 million wmt allocation, with average Ni content 1.86% and SiO2/MgO ratio 2.20. Then, monthly production scheduling is carried out to produce the mine boundary for each quarter, which is used as guidance in mining operation. After mining process, stockpile management and ore blending strategy are carried out so that the nickel processing plant target can be achieved steadily. By using the ore blending strategy, Gag Nickel mine can apply conservation by optimizing marginal grade reserve so it can be fully utilized.